Search based software engineering : 5th International Symposium, SSBSE 2013, St. Petersburg, Russia, August 24-26, 2013. Proceedings - Zhang, Yuanyuan; Ruhe, Gunther (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the Fifth International Symposium on Search-Based Software Engineering, SSBSE 2013, held in St. Petersburg, Russia. The 14 revised full papers, 6 revised short papers, and 6 papers of the graduate track presented together with 2 keynotes, 2 challenge track papers and 1 tutorial paper were carefully reviewed and selected from 50 initial submissions. Search Based Software Engineering (SBSE) studies the application of meta-heuristic optimization techniques to various software engineering problems, ranging from requirements engineering to software testing and maintenance.